Innovative pH-triggered antibacterial nanofibrous coatings for enhanced metallic implant properties - Kloster, Gianina A.; Rivero, Guadalupe; Ballarre, Josefina; Herrera Seitz, M. Karina; Ceré, Silvia M.; Abraham, Gustavo A. (Frontiers in Materials, 2024)
Metallic stainless steel bone implants are widely used due to their excellent mechanical properties, low cost, and ease of fabrication. Nanofibrous composite polymers have been proposed as coatings to promote biocompatibility and osseointegration, thanks to their biomimetic morphology that resembles the extracellular matrix. However, critical practical issues are often overlooked in the literature. For instance, applying coatings to implants with different shapes presents a significant technological challenge, as does evaluating viable sterilization procedures for hybrid devices containing electrospun polymers. In addition, infections pose a risk in any surgical procedure and can lead to implant failure, there is a need for antimicrobial prevention during surgery as well as in the short term afterward. In this work, we propose a new and straightforward method for manufacturing nanofibrous composite coatings directly on thin cylindrical-shaped metallic implants. Poly(ε-caprolactone) (PCL) nanofibers containing bioactive glass microparticles were electrospun onto stainless steel wires and then post-treated using two different strategies to achieve both hydrophilicity and surface disinfection. To address antimicrobial properties, amoxicillin-loaded Eudragit®E nanofibers were co-electrospun to impart pH-selective release behavior in event of a potential infection. The resulting composite hybrid coatings were characterized morphologically, physically, chemically, and electrochemically. The antibacterial behavior was evaluated at different media, confirming the release of the antibiotic in the pH range where infection is likely to occur. The impact of this study lies in its potential to significantly enhance the safety and efficacy of orthopedic implants by offering a novel, adaptable solution to combat infection. By integrating a pH-responsive drug delivery system with antimicrobial coatings, this approach not only provides a preventive measure during and after surgery but also addresses the growing issue of antibiotic resistance by targeting specific infection conditions.